Indigenizing Social Disorganization Theory: An Exploration of Victimization in Native Communities - Gilbert, Sheena L. (Crime & delinquency, 2025)
Prior research that is grounded in social disorganization theory has found that community characteristics impact victimization. Despite the robust literature using social disorganization theory, very few studies have used this theory to examine violence and victimization in Indigenous communities. The following study examined counties in 14 states that fully or partially contained reservation land (N = 251) to determine the applicability of this theory to a unique population. Findings indicate that social disorganization theory can be used to predict victimization in Indigenous communities. In addition, a more culturally tailored model (i.e., Indigenized model) predicted victimization slightly better than the traditional model, however, the difference between the models was not significant. We conclude with a discussion of our findings and offer future directions for research.